The Effects of Synbiotic “Bifidobacterium lactis B94 plus Inulin” Addition on Standard Triple Therapy of Helicobacter pylori Eradication in Children - Gonca Handan Ustundag; Halime Altuntas; Yasemin Dilek Soysal; Furuzan Kokturk (Canadian Journal of Gastroenterology and Hepatology)
Aim. The aim of this study is to evaluate the effects of the synbiotic Bifidobacterium lactis B94 plus inulin addition to the standard triple therapy on Helicobacter pylori (H. pylori) infection eradication rates. Methods. Children aged 6–16 years who had biopsy proven H. pylori infection were randomly classified into two groups. The first group received the standard triple therapy consisting of amoxicillin + clarithromycin + omeprazole. The second group was treated with the standard triple therapy and Bifidobacterium lactis B94 (5 × 109 CFU/dose) plus inulin (900 mg) for 14 days, concurrently. Eradication was determined by 14C-urea breath test 4–6 weeks after therapy discontinuation. Results. From a total of 69 H. pylori infected children (F/M = 36/33; mean ± SD = 11.2 ± 3.0 years), eradication was achieved in 20/34 participants in the standard therapy group and 27/35 participants in the synbiotic group. The eradication rates were not significantly different between the standard therapy and the synbiotic groups [intent-to-treat, 58.8% and 77.1%, resp., p = 0.16; per-protocol, 64.5% and 81.8%, resp., p = 0.19]. There was no difference between the groups in terms of symptom relief (p = 0.193). The reported side effects were ignorable. Conclusion. Considering the eradication rates, synbiotic addition to therapy showed no superiority over the standard triple therapy conducted alone. This trial is registered with NCT03165253.